Improving Computational Thinking & Creative Problem Solving: ESD & Micro:bit for Climate - Umam, Ahmad Naufal; Herlina, Kartini; Abdurrahman, Abdurrahman; Ertikanto, Chandra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This study aims to validate the Student Worksheet titled